2016
DOI: 10.1093/imrn/rnw147
|View full text |Cite
|
Sign up to set email alerts
|

Silting Modules over Commutative Rings

Abstract: Abstract. Tilting modules over commutative rings were recently classified in [12]: they correspond bijectively to faithful Gabriel topologies of finite type. In this note we extend this classification by dropping faithfulness. The counterpart of an arbitrary Gabriel topology of finite type is obtained by replacing tilting with the more general notion of a silting module.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…One of the main results of this paper is based on some recent results of Hrbek and Angeleri Hügel-Hrbek [11,1]. We show that whenever u : R −→ U is a homological ring epimorphism and U is an R-module of projective dimension 1, it follows that U is a flat R-module.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…One of the main results of this paper is based on some recent results of Hrbek and Angeleri Hügel-Hrbek [11,1]. We show that whenever u : R −→ U is a homological ring epimorphism and U is an R-module of projective dimension 1, it follows that U is a flat R-module.…”
Section: Introductionmentioning
confidence: 81%
“…The R-module U ⊕ U/R is 1-silting by [13,Example 6.5], and a 2-term projective resolution of the complex U ⊕ K • is the related silting complex. Hence C = Hom Z (U ⊕ U/R, Q/Z) is a cosilting R-module of cofinite type [1,Corollary 3.6]. The cosilting class associated with C consists of all the u-torsion-free R-modules, and the torsion class in the cosilting torsion pair is the class of all u-torsion R-modules.…”
Section: When Is the Class Of Torsion Modules Hereditary?mentioning
confidence: 99%
See 2 more Smart Citations
“…In [15], it is shown that, for finitedimensional algebras of finite representation type, silting modules are in bijection F. Pop with universal localizations. Recently, in [4], the authors give a classification of silting modules over commutative rings, establishing a bijective correspondence of them with Gabriel filters of finite type. The dual notion, of cosilting module, was independently introduced in [7,17], as a generalization of the concept of cotilting module.…”
Section: Introductionmentioning
confidence: 99%